Postpartum anal incontinence in women with and without obstetric anal sphincter injuries - Everist, R.; Burrell, M.; Mallitt, K.A.; Parkin, K.; Patton, Vicki; Karantanis, E. (2020)
Introduction and hypothesis: Postpartum anal incontinence is common and distressing for women. We sought to look at the prevalence of anal incontinence in women who sustained obstetric anal sphincter injuries (OASI) compared with women who did not, and factors leading to these symptoms during the postpartum period. Methods: A total of 129 primiparous women sustaining OASI were compared with 131 women who did not (controls). They were contacted at approximately 6–10 weeks postpartum to obtain information on their symptoms of anal incontinence (AI). The data underwent univariate and multivariate analysis. Results: There was no difference in the prevalence of AI symptoms, occurring in 30% of women with OASI, and 23% of women without at 6–10 weeks postpartum; however, in women with high-grade tears the prevalence was 59%. Severe OASI (grade 3c and 4) was associated with an increased prevalence of both AI and severe AI, whereas forceps delivery and increasing maternal age were associated with an increased prevalence of severe AI only. Conclusion: Women with less severe (grade 3a and 3b) OASI do not experience a higher prevalence of AI than women without OASI in the postpartum period. Higher grade (3c and 4) tears, forceps delivery and increasing maternal age are associated with higher rates of AI. These factors should be avoided where possible to reduce postpartum AI. All women should be warned of the 23–30% chance of experiencing some mild AI in this period. Whether these symptoms are transient or long-lasting requires further investigation.